A Study of e-content through e-learning Viewpoints of Researchers - Rana, Shipra; Singh, Nain (JOURNAL OF INDIAN EDUCATION, 2020)
The meaning and nature of education is getting new shape and perspective due to developments in the field of Information and Communication Technology. The use of Information and Communication Technology for effective learning in a knowledge-based society has travelled a long distance. E-learning has become the most strong and effective tool for twenty first century in the educational system. It has modernised the entire process of teaching and learning through the use of variety of techniques by designing of e-content in new perspectives. Now-a-days, development of quality e-content and its effect on the learning level of students has become one of the most preferred subjects for researchers to research on. The researchers, in this paper, tried to find out its root by emphasising the investigated steps to peep deeply into the origin of e-learning in India, and analysed the various researchers’ works on e-contents through e-learning to visualise the scope for further research to be conducted in this field of investigation.